Kuntowijoyo's Concept of Scientification of Islam and its Relevance for Post-Secular Society: Konsep Saintifikasi Islam Menurut Kuntowijoyo dan Relevansinya bagi Masyarakat Pasca Sekuler - Mahendra, Richo Bintang; Rizkita, Muhammad; Nurcholish, Ahmad (Jurnal Filsafat Indonesia, 2024)
Modernity is a period that gave birth to the phenomenon of secularization of science. Religion was only placed in the private sphere. However, in the 21st century, religion is now starting to appear in the public sphere. Religious discourse can appear in the exchange of discourse in the public sphere. This paper discusses the discourse of religion as a paradigm in the development of sciences in Kuntowijoyo's idea of Scientification of Islam as an new framework to viewing relationship between religion and sciences. In addition to describing descriptively, this paper also tries to see the relevance of Kuntowijoyo's ideas in the social context of post-secular society. The research method this study is Hans-Georg Gadamer's contextual interpretation. Gadamer states that the understanding process is a fusion between the horizon of the writer and the reader. The method is used by the author in seeing the relevance of the concept of Scientification of Islam to the reality of post-secular society. The results of this study show that descriptively Scientification of Islam is an effort to demystify, which is to draw the text into the human social context. Demystification of Islam can be a new discourse for the development of Islamic thought in order to realize Islam rahmatan lil alamin. Efforts in realizing Islam rahmatan lil alamin are achieved through two stages that are interrelated with each other, namely the integralization of Quranic discourse with general sciences and objectification of Quranic discourses so that they can be accepted by society in general. The concept of Scientification of Islam offered by Kuntowijoyo can be an effort of Muslims in translating particular theological language into a generally accepted language, so that the Islamic discourses contained in the Quran can be relevant and accepted in general by all secular societies in the context of post- secular society.